Electromagnetic Analysis of CFETR Vacuum Vessel During Plasma Vertical Displacement Event. (3rd April 2022) - Tang, Le; Ran, Hong; Cai, Lijun; Huang, Yuncong; Hou, Jilai; Song, Binbin
Abstract: The vacuum vessel (VV) of the China Fusion Engineering Test Reactor (CFETR) performs many functions, but its main function is to provide a high-quality, ultra-high-vacuum environment for plasma operation. The electromagnetic load acts on the VV and its ports during a plasma vertical displacement event (VDE). This paper adopts a new simulation method of the plasma current during transient electromagnetic analysis. The distribution of the electromagnetic load on the VV shells, the upper ports, the equatorial ports, and the lower ports is entirely displayed. The structural stress under the electromagnetic load during a VDE was obtained by electromagnetic-structural coupling. According to the structural analysis, the results indicate that the VV can meet the structural strength and stiffness requirement.